Effects Of Different Watering Regimes On Foliar Spectral Reflectance And Chlorophyll Content Of Jatropha curcas Linn. - Sulok, K.M.T.; Zainudin, S.R; Hassim, M.I; Suhaili, S. (Malaysian Society of Plant Physiology, 2012)
The influence of high and reduced water availability on the changes in foliar spectral reflectance and chlorophyll of J. curcas were investigated. The field experiment conducted was based on a completely randomized design (CRD) with four treatments replicated three times. Each replicate consisted of two plants with a total of 24 plants altogether. Treatments were: (i) Rainfed (W0) – plants were watered at field capacity > -0.03 MPa, (ii) Mild water stress (W1) – watering was carried out to maintain soil water potential between - 0.30 and -0.10 MPa, (iii) Moderate water stress (W2) – watering was carried out to maintain soil water potential between -1.0 and -0.8 MPa, and (iv) extreme water stress (W3) – plants were grown at soil permanent wilt point <-1.50 MPa. The well-watered plants responded by showing significantly (p <0.05) better height growth. Result shows mean reflectance spectra increased with increasing water stress. As water stress indicator, foliar spectral analysis showed high reflectance which was primarily attributed to a 41 % reduction in chlorophyll concentration. The percentage reflectance at 550 (R550), structure independent pigment index (SIPI), and photochemical reflectance index (PRI) showed a strong relationship with foliar chlorophyll content (SPAD). These results suggested that well-watered plants at soil water field capacity (-0.03 MPa) showed greener and healthier leaf growth compared to that of the water-stressed plants